T.I.M.E.L.I.N.E / Afifah Fadhlullah - Fadhlullah, Afifah (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems compiled from interested 118 lecturers and academicians from UiTM and other higher learning institutions